A Unique Saccharomyces cerevisiae × Saccharomyces uvarum Hybrid Isolated From Norwegian Farmhouse Beer: Characterization and Reconstruction - Krogerus, Kristoffer; Preiss, Richard; Gibson, Brian (Frontiers in Microbiology, 2018)
An unknown interspecies Saccharomyces hybrid, “Muri,” was recently isolated from a “kveik” culture, a traditional Norwegian farmhouse brewing yeast culture (Preiss et al., 2018). Here we used whole genome sequencing to reveal the strain as an allodiploid Saccharomyces cerevisiae × Saccharomyces uvarum hybrid. Phylogenetic analysis of its sub-genomes revealed that the S. cerevisiae and S. uvarum parent strains of Muri appear to be most closely related to English ale and Central European cider and wine strains, respectively. We then performed phenotypic analysis on a number of brewing-relevant traits in a range of S. cerevisiae, S. uvarum and hybrid strains closely related to the Muri hybrid. The Muri strain possesses a range of industrially desirable phenotypic properties, including broad temperature tolerance, good ethanol tolerance, and efficient carbohydrate use, therefore making it an interesting candidate for not only brewing applications, but potentially various other industrial fermentations, such as biofuel production and distilling. We identified the two S. cerevisiae and S. uvarum strains that were genetically and phenotypically most similar to the Muri hybrid, and then attempted to reconstruct the Muri hybrid by generating de novo interspecific hybrids between these two strains. The de novo hybrids were compared with the original Muri hybrid, and many appeared phenotypically more similar to Muri than either of the parent strains. This study introduces a novel approach to studying hybrid strains and strain development by combining genomic and phenotypic analysis to identify closely related parent strains for construction of de novo hybrids.